Role of Extracellular Vesicle-Based Cell-to-Cell Communication in Multiple Myeloma Progression - Ilaria Saltarella (MDPI AG, 2021)
Multiple myeloma (MM) progression closely depends on the bidirectional crosstalk between tumor cells and the surrounding microenvironment, which leads to the creation of a tumor supportive niche. Extracellular vesicles (EVs) have emerged as key players in the pathological interplay between the malignant clone and near/distal bone marrow (BM) cells through their biologically active cargo. Here, we describe the role of EVs derived from MM and BM cells in reprogramming the tumor microenvironment and in fostering bone disease, angiogenesis, immunosuppression, drug resistance, and, ultimately, tumor progression. We also examine the emerging role of EVs as new therapeutic agents for the treatment of MM, and their potential use as clinical biomarkers for early diagnosis, disease classification, and therapy monitoring.